LETTER TO EDITOR - Asma Shabbir (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
Dear Editor, I am writing to express my admiration for the Journal of Pakistan University of Medical and Health Sciences JPUMHS and its commitment to publishing high quality research in the field of medical and health sciences.